Xiaomi Mi 8 smartphone GNSS data quality analysis and single‐frequency RTK positioning performance evaluation. Issue 9 (5th August 2020) - Sun, Wei; Li, Yuying; Duan, Shunli
Abstract : In this study, the authors mainly explore the relationship between the data quality of smartphones equipped with global navigation satellite system (GNSS) modules and the accuracy and reliability of single‐frequency real‐time kinematic (RTK) positioning. Specifically, the visible satellite number, code minus carrier and the signal‐to‐noise ratio of the GNSS raw observations were evaluated through static experiments and dynamic experiments, and the performance difference between single‐frequency global positioning system (GPS) RTK and single‐frequency BeiDou Navigation Satellite System (BDS) RTK positioning was compared and analysed. In the static experiment, the average values of visible satellites of BDS and GPS in Xiaomi Mi 8 smartphone are 7.4 and 8.4, respectively. The average code minus carrier error of GPS is 5.234 m, the BDS is 5.518 m, and the average signal‐to‐noise ratio of GPS is ∼29.092 dB Hz and the BDS is ∼28.718 dB Hz. The data quality of the dynamic experiment is similar to the static experimental result. The positioning accuracy obtained by the static experiment from the single‐frequency GPS RTK and single‐frequency BDS RTK in the east/north/up (E/N/U) directions is 0.146/0.555/0.464 m and 0.843/0.287/0.317 m, respectively. The instability of BDS‐locked satellite in dynamic experiment results the positioning accuracy of BDS RTK is lower than that of GPS.